Strategi Pemerintahan dalam Upaya Penurunan Angka Prevalensi Stunting di Kota Tanjungpinang - Ayu Pebrianti; Yudhanto Satyagraha Adiputra; Ella Afnira (Jurnal Hukum dan Sosial Politik, 2025)
The city of Tanjungpinang has successfully reduced the prevalence of stunting consistently from 2021 to 2023, from 18,8% in 2021 to 15,7% in 2022, and to 15,2% in 2023 compared to six other regencies/cities in the Riau Islands Province. This research aims to identify the strategies used by the DKP2KB of Tanjungpinang City in efforts to reduce the prevalence of stunting from 2021 to 2023. Using a qualitative research method with a case study approach, there were nineteen informants, and data collection techniques included interviews and documentation. This research uses the strategy theory from Geoff Max Mulgan, which includes purposes, environments, directions, actions, and learning. The findings obtained are, (1) Purposes: in terms of output to achieve the national target of 14% with a performance target of 3.48% from 2021-2023 and outcomes in the form of improving the quality of human resources and the quality of life of the community. (2) Environments: still facing pollution constraints, suboptimal parenting patterns, and difficult economic conditions for the community. (3) Directions: includes commands in regulations, coordination through forums, building motivation, and effective communication. (4) Actions: activities carried out, namely sensitive interventions involving cross-sector, cross-program, and private sectors to facilitate assistance and innovation, while specific interventions involve intervening in public health. (5) Learning: all activities have been carried out well, as evidenced by the national survey results showing a decrease in stunting prevalence, although the target of 14% has not yet been reached, and the stunting program performance targets have been successfully achieved. However, the overall effectiveness of the program heavily depends on active community participation. Therefore, to address this, the researchers suggest that the government encourage knowledge, awareness, and participation from the community.